Imaging of Liver Tumors Using Surface-Enhanced Raman Scattering Nanoparticles - Andreou, Chrysafis; Neuschmelting, Volker; Tschaharganeh, Darjus-Felix; Huang, Chun-Hao; Oseledchyk, Anton; Iacono, Pasquale; Karabeber, Hazem; Colen, Rivka R; Mannelli, Lorenzo; Lowe, Scott W; Kircher, Moritz F (ACS nano, 2016)
Complete surgical resection is the ideal first-line treatment for most liver malignancies. This goal would be facilitated by an intraoperative imaging method that enables more precise visualization of tumor margins and detection of otherwise invisible microscopic lesions. To this end, we synthesized silica-encapsulated surface-enhanced Raman scattering (SERS) nanoparticles (NPs) that act as a molecular imaging agent for liver malignancies. We hypothesized that, after intravenous administration, SERS NPs would avidly home to healthy liver tissue but not to intrahepatic malignancies. We tested these SERS NPs in genetically engineered mouse models of hepatocellular carcinoma and histiocytic sarcoma. After intravenous injection, liver tumors in both models were readily identifiable with Raman imaging. In addition, Raman imaging using SERS NPs enabled detection of microscopic lesions in liver and spleen. We compared the performance of SERS NPs to fluorescence imaging using indocyanine green (ICG). We found that SERS NPs delineate tumors more accurately and are less susceptible to photobleaching. Given the known advantages of SERS imaging, namely, high sensitivity and specific spectroscopic detection, these findings hold promise for improved resection of liver cancer.